Obstructive Sleep Apnea Syndrome in Children with 22q11.2 Deletion Syndrome after Operative Intervention for Velopharyngeal Insufficiency - Crockett, David Jeffrey; Goudy, Steven L.; Chinnadurai, Sivakumar; Wootten, Christopher Todd (Frontiers in Pediatrics, 2014)
Introduction: Surgical treatment of velopharyngeal insufficiency (VPI) in 22q11.2 deletion syndrome is often warranted. In this patient population, VPI is characterized by poor palatal elevation and muscular hypotonia with an intact palate. We hypothesize that 22q11.2 deletion patients are at greater risk of obstructive sleep apnea (OSA) after surgical correction of VPI, due, in part, to their functional hypotonia, large velopharyngeal gap size, and the need to surgically obstruct the velopharynx. Methods: We performed a retrospective analysis of patients with 22q11.2 deletion syndrome treated at a tertiary pediatric hospital between the years of 2002-2012. The incidence of VPI, need for surgery, post-operative polysomnogram, post-operative VPI assessment, and OSA treatments were evaluated. Results: Forty-three patients (18 males, 25 females, ages 1-14 years) fitting the inclusion criteria were identified. Twenty-eight patients were evaluated by speech pathology due to hypernasality. Twenty-one patients had insufficient velopharyngeal function and required surgery. Fifteen underwent pharyngeal flap surgery, three underwent sphincter pharyngoplasty, two underwent Furlow palatoplasty, and one underwent combined sphincter pharyngoplasty with Furlow palatoplasty. Of these, eight had post-operative snoring. Six of these underwent polysomnography. Four patients were found to have OSA based on the results of the polysomnography (average apnea/hypopnea index of 4.9 events/hour, median=5.1, SD=2.1). Two required continuous positive airway pressure (CPAP) due to moderate OSA. Conclusion: Surgery is often necessary to correct VPI in patients with 22q11.2 deletion syndrome. Monitoring for OSA should be considered after surgical correction of VPI due to a high occurrence in this population. Furthermore, families should be counseled of the risk of OSA after surgery and the potential need for treatment with CPAP.